An energy proficient load balancing routing scheme for wireless sensor networks to maximize their lifespan in an operational environment - Adil, Muhammad; Khan, Rahim; Ali, Jehad; Roh, Byeong Hee; Hoai Ta, Qui Thanh; Almaiah, Mohammed Amin (IEEE Access, 2020)
Owing to the limited resources of sensor nodes, we propose an efficient hybrid routing scheme using a dynamic cluster-based static routing protocol (DCBSRP), leveraging the ad hoc on-demand distance vector (AODV) routing protocol and low-energy adaptive clustering hierarchy (LEACH) protocol. In the proposed scheme, the cluster head (CH) nodes are formed dynamically for a fixed interval, whereas static routing is applied in the designated clusters by utilizing the AODV routing protocol. The static routing condition of the proposed scheme limits all connected nodes of the cluster for a defined interval of time (T) to share their collected information through a specific CH node. Once the time (T) interval is completed, all ordinary nodes connected with the specific CH are released and they are free to advertise their CH candidateship within the network. Likewise, the node receiving the maximum number of route replies (RREPs) is selected as the next CH node in the vicinity of deployed sensor nodes. However, with the DCBSRP protocol, the recently selected CH node does not advertise its candidateship for five consecutive cycles and acts as an ordinary node. The simulation result shows significant improvement in the lifetime and participation of ordinary nodes in the network until the end-stage of the network. In the proposed scheme, the participation of ordinary nodes in the network is 95.9 %, which not only balances load between participating nodes but also improves the network lifetime in the presence of field-proven schemes. Moreover, the simulation results show an out-performance of rival schemes in terms of communication cost, end to end delay, throughput, packet lost ratio, and energy consumption.
Keywords: Ad hoc on demand distance vector routing protocols; AODV routing protocol; Communication cost; End to end delay; Load-balancing routing schemes; Low energy adaptive clustering hierarchies (LEACH); Network lifetime; Operational environments; Load balancing; Routing protocol; Sensor nodes; Sensor nodes energy; Wireless communication; Wireless sensor networks; WSNs lifespan